1995
DOI: 10.1111/j.1365-2095.1995.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary DP/DE ratio on apparent digestibility, growth and nitrogen and phosphorus retention in rainbow trout, Oncorhynchus Mykiss (Walbaum)

Abstract: The effect of DPDE ratio in diets for rainbow trout, Oncorhynchus mykiss (Walbaum), was investigated. To evaluate growth and body composition, groups of trout were fed three experimental diets with a constant level of gross energy (25.4 & 0.12 MJ kg-' dry matter (DM)) and different digestible proteiddigestible energy (DPIDE) ratios (diet A, 16. 35; diet B, 17.21; diet C, 18.23 g MJ-I).Fat, protein and energy digestibility coefficients were not affected by the DPDE ratio of the diets. Growth and feed utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
0
12
2
Order By: Relevance
“…Thus, the improvement in fish performance that accompanied the use of higher energy (lipid) diets required a concomitant increase in dietary CP. This differs from the findings with salmonids (Cho 1992;Hillestad & Johnsen 1994;Lanari, D'Agaro & Ballestrazzi 1995), in which high-lipid diets have been used to obtain considerable sparing of dietary CP. Further studies are needed to determine the usefulness of high-energy (lipid) diets for barramundi.…”
Section: Discussioncontrasting
confidence: 97%
“…Thus, the improvement in fish performance that accompanied the use of higher energy (lipid) diets required a concomitant increase in dietary CP. This differs from the findings with salmonids (Cho 1992;Hillestad & Johnsen 1994;Lanari, D'Agaro & Ballestrazzi 1995), in which high-lipid diets have been used to obtain considerable sparing of dietary CP. Further studies are needed to determine the usefulness of high-energy (lipid) diets for barramundi.…”
Section: Discussioncontrasting
confidence: 97%
“…Lee and Putnam 17 also observed that inclusion of up to 24% fat in 36–53% protein level diets for rainbow trout had no negative influence on the growth and feed conversion. In addition, beneficial effects of current salmonid diets containing high levels of fat have been demonstrated 18,19 . However, utilization of fat and carbohydrate by trout under self‐feeding conditions seems slightly different to the studies conducted with the manual meal‐feeding method mentioned above, that is, the highest fat to carbohydrate ratio diet (S9) resulted in somewhat reduced growth and protein utilization compared to the diet with the second highest ratio (S18).…”
Section: Discussionmentioning
confidence: 96%
“…Effects of extruded high-energy diets on growth, feed conversion and body composition have recently been reported. Most of these experiments have been conducted with rainbow trout (Alsted & Jokumsen 1990;Alsted 1991;Lanari et al 1995) and small-sized Atlantic salmon in sea water (Johnsen & Wandsvik 1991;Johnsen et al 1993;Hillestad & Johnsen 1994). Wathne (1995) and Einen & Roem (1997) reported results from shorterterm experiments and Aksnes (1995) from long-term experiments with slaughter-sized Atlantic salmon fed extruded high-energy diets.…”
Section: Introductionmentioning
confidence: 99%